Impact of Warning Pop-Up Messages on the Gambling Behavior, Craving, and Cognitions of Online Gamblers: A Randomized Controlled Trial - Caillon, Julie; Grall-Bronnec, Marie; Saillard, Anaïs; Leboucher, Juliette; Péré, Morgane; Challet-Bouju, Gaelle (Frontiers in Psychiatry, 2021)
Background: Many features of Internet gambling may impact problem severity, particularly for vulnerable populations (availability, anonymity, a convenience and ease of play, digital forms of payment, and a higher level of immersion). To prevent the risks associated with excessive gambling and to inform gamblers, we need responsible gambling strategies. Gambling-related warning messages are one possible strategy that can help minimizing gambling-related harm. Methods: Our experimental study aimed to evaluate the effectiveness of self-appraisal and informative pop-up messages compared to a control condition (blank pop-up messages), for both at-risk and low risk/ non-problem Internet gamblers according to their favourite type of game, in a semi naturalistic setting and with a 15-day follow-up. During the experimental session, participants were invited to gamble on their favourite website with their own money in the laboratory. Effectiveness was investigated through the impact of pop-ups on gambling behaviour (money wagered and time spent), craving, cognitive distortions, and gambling experience, taking into account message recall. We analysed data from 58 participants, playing preferentially either to skill and chance bank games (sports betting, horse race betting) and skill and chance social games (poker). Results: We observed a significant decrease in the illusion of control for at-risk gamblers in the informative pop-up condition at the 15-day follow-up. A significant effect of self-appraisal pop-ups compared to blank pop-up messages was also demonstrated only for sport and horse bettors, with a decrease on time spent gambling and an increase of gambling-related expectancies at the follow-up. Finally, we also observed that a majority of the participants were disturbed and irritated by pop-ups during their gambling session. Conclusions: The results of our study demonstrated the limited impact of pop-up warning messages on gambling behaviour and cognition in Internet gamblers according to the type of game and the status of gamblers. The limited impact of warning messages on gambling behaviour and the inconvenience of the pop-ups for Internet gamblers lead us to only consider warning messages as one piece of a larger responsible gambling strategy. Trial registration number: NCT01789580 on February 12, 2013